Nonlinearity-induced time-varying harmonic dynamic axle load and its impact on dynamic stability of car–trailer combinations. Issue 6 (2nd June 2016) - Zhang, Ning; Xiao, Hong; Winner, Hermann
ABSTRACT: A nonlinearity-induced time-varying harmonic dynamic axle load is found in the road test of a car–trailer combination. To understand its influence on system dynamic stability, a corresponding linear single-track model (STM) is proposed. System dynamic stability is described and sensitivity analysis for the system parameters is achieved. The contribution of the harmonic force is quantified by a derived effective axle load. Because the harmonic effect might be time varying in practice, a time–frequency analysis-based parameter identification method is introduced. Experimental study shows that a time-varying harmonic effect really exists. A yaw-rate-based simulation method is designed to simulate this behaviour. The sensitivity analysis of the influence of the harmonic amplitude or phase on dynamic stability is performed with a simulation study. With appropriate modification of the harmonic amplitude and phase shift applied in selected time windows, the time-varying system characteristics in the road test can be simulated very well.